2010
DOI: 10.1002/nau.20869
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic cystopathy is associated with PARP/JNK/ mitochondrial apoptotic pathway‐mediated bladder apoptosis

Abstract: These results indicate that bladder apoptosis is involved in diabetic cystopathy via activation of the PARP/JNK/mitochondrial apoptotic pathway. These findings may be used to develop novel therapies for patients with diabetic bladder dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…First, the functional changes of diabetic bladder are presented in divergent ways. The peak micturition pressures of the diabetic bladder 12 weeks after induction were decreased in our study, whereas other studies reported an increase in this parameter 5, 37. Such discrepancies in the alteration of bladder function in model systems may act as an obstacle to the performance of quantitative analyses.…”
Section: Discussioncontrasting
confidence: 77%
“…First, the functional changes of diabetic bladder are presented in divergent ways. The peak micturition pressures of the diabetic bladder 12 weeks after induction were decreased in our study, whereas other studies reported an increase in this parameter 5, 37. Such discrepancies in the alteration of bladder function in model systems may act as an obstacle to the performance of quantitative analyses.…”
Section: Discussioncontrasting
confidence: 77%
“…Apoptosis, which can result in excessive cell loss, has been reported to play a critical role in the development of DCP by several studies . As an important subcelluar network with the membranous structure, the endoplasmic reticulum (ER) is associated with the intrinsic pathway of apoptosis and has been suggested to be pivotal in the lipid biosynthesis, protein folding, and protein maturation .…”
Section: Introductionmentioning
confidence: 99%
“…The urothelium had detached from the underlying mucosa, and the discontinuities of the apical plasma membranes indicated the urothelium was undergoing cell death . In another study of diabetic rats, Li et al showed that urothelial cell apoptosis was involved in diabetic cystopathy via activation of poly (ADP‐ribose) polymerase, c‐Jun N‐terminal kinase, and the mitochondrial apoptotic pathway . In this study, OAB patients, regardless of DM, had significant disruption of urothelial barrier function, which could result in the migration of noxious urinary substances into the underlying tissue causing suburothelial inflammation.…”
Section: Discussionmentioning
confidence: 61%